Neutrophil-Related Oxidants Drive Heart and Brain Remodeling After Ischemia/Reperfusion Injury - Carbone, Federico; Bonaventura, Aldo; Montecucco, Fabrizio (Frontiers in Physiology, 2020)
The inflammatory response characterizing ischemia/reperfusion injury (IRI) has a critical role in determining not only the extension of myocardial and brain infarcts, but also functional recovery and long-term outcomes. Reactive oxygen species (ROS) are of great relevance in the post-ischemic period being involved in tissue repair through the clearance of dead cells and debris. Especially neutrophils play a critical role in redox signaling, due to their early recruitment and the large variety of ROS released. Noteworthy, ROS generated during IRI has a relevant role in both myocardial healing and activation of neuroprotective pathways. Furthermore, anatomical and functional differences contribute to the different response in myocardial tissue and brain, despite a significant gene overlapping. Nevertheless, the exaggerated activation of this signaling system can result in adverse consequences, such as cell apoptosis and extracellular matrix degradation. In light of that, blocking ROS cascade might have therapeutic implication for cardiomyocyte and neuronal loss after acute ischemic events. Despite the variety of anti-oxidants tested, the translation from pre-clinical models to clinical trials have so far failed because of differences between humans and animals, difficulty of agents to penetrate into specific cellular organs and specifically unravel oxidant and anti-oxidant pathways. Here, we will update the current knowledge on ROS cascade in IRI, focusing on the role of neutrophils. Furthermore, we will discuss the current evidence of ROS blockade as therapeutic approach for myocardial infarction and ischemic stroke.